Enhancing Interfacial Adhesion and Toughness of Flax Fabric/Polylactic Acid Biocomposites Through Polyethylene Glycol Treatment - Altinbay, Aylin (WILEY, 2026)
The development of fully biodegradable composites has gained significant attention as a sustainable alternative to traditional fiber-reinforced materials. This study focuses on enhancing the interfacial adhesion and toughness of flax fiber-reinforced polylactic acid (PLA) biocomposites. PLA is inherently brittle, and its hydrophobic nature restricts interfacial adhesion with hydrophilic natural fibers, leading to inefficient stress transfer. To address these limitations, biaxial non-crimp flax fabrics were modified using an aqueous polyethylene glycol (PEG)-based treatment-a simple, green, and cost-effective approach that avoids hazardous chemical solvents. PEG molecular weights of 1500 and 6000 g/mol were investigated at various concentrations to determine their influence on interfacial and mechanical performance. The modified fabrics were consolidated with PLA films through hot compression molding. Mechanical characterization was performed through tensile, flexural, interlaminar shear, and impact testing. The results demonstrate that a 3 wt% concentration of PEG 6000 provides an optimal balance of properties, increasing the impact strength from 25 to 51 kJ/m2 and doubling the flexural strain-to-failure to 10%. The results indicate that the molecular weight of PEG plays a crucial role in balancing interfacial bonding and matrix plasticization. These findings demonstrate that this environmentally friendly and industrially scalable strategy effectively enhances the energy absorption capability of flax/PLA biocomposites, providing a tunable framework for high-performance structural applications in the automotive sector.
Keywords: biodegradable composites; flax fabric; polyethylene glycol; polylactide; toughness; POLY(LACTIC ACID); FIBER; Materials Science; Polymer Science